Analysis of match quality in League of Legends across different times of the day - Peer, Vlastimil (2024)
This bachelor thesis investigates the influence of time of day on match quality in League of Legends, a popular online game. It explores how players' performance in League of Legends varies across different time periods, considering factors like circadian rhythms and daily activities. By leveraging Riot Games' API, the study analyzes a large dataset and implements LASSO regression, to predict match quality. The results show significant variations in gameplay quality, with early afternoon being optimal for the most competitive games, and late-night to early morning sessions showing decreased quality. This study provides insights for players looking for optimal gaming times and contributes to understanding online gaming behavior in relation to time of day.